Indeks Massa Tubuh Menurut Umur sebagai Indikator Persen Lemak Tubuh pada Remaja - Retno Ayu Widyastuti; Ali Rosidi (Universitas Muhammadiyah Semarang, 2018)
Health impact which caused by overnutrition is related by excess body fat. Thus, nutritionalstatus monitoring in adolescent is crucial because the prevelance of overnutrition in adolescentincreased per years. Body Mass Index per age (BMI/A) is generally used to determine nutritionalstatus, but incapable to measure overnutrition related excess body fat precisely. Body fat percentageis used to determine overnutrition but special equipment and capability are required. The purposeof the study is to analyze correlation between BMI/A and body fat percentage and verify BMI/A’ssensitivity-specificity as body fat percentage’s indicator. In this cross-sectional study, 82 adolescentsfrom SMAN 47 Jakarta are chosen to participate by simple random sampling. Body fat percentageand BMI/A are being taken by anthropometric instruments, where body fat percentage used to bethe gold standart. Using BMI/A, the prevalence of overnutrition is 23,2%. Its lower than using thegold standart (35,4%). The correlation between BMI/A and percent body fat is r=0,814; p=0,000.Their sensitivity is 55,17% while their spesificity is 94,34%. Eventhough there is strong correlation,BMI/A is less sensitive as body fat percentage’s indicator to determine nutritional status inadolescent. Body fat measurement is needed to validate value of BMI/A.Key words: adolescent, BMI/A, body fat percentage